1985
DOI: 10.1002/j.1460-2075.1985.tb03976.x
|View full text |Cite
|
Sign up to set email alerts
|

beta s-Crystallin: structure and evolution of a distinct member of the beta gamma-superfamily.

Abstract: The nucleotide sequence of the cDNA of bovine lens beta s‐crystallin has been determined, and the derived amino acid sequence has been confirmed by amino acid compositions and partial sequences of the tryptic peptides of this monomeric protein. beta s‐Crystallin has a length of 177 residues, corresponding to a mol. wt. of 20 773, and a blocked N‐terminal serine. Comparison of beta s with the known sequences of other beta‐ and gamma‐crystallins, and computer construction of a phylogenetic tree of these sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 38 publications
(32 reference statements)
6
45
1
Order By: Relevance
“…Crystallins have been observed previously in lenses of the mole rat, S. ehrenbergi, by immunofluorescence (29). In addition, mole rat shsp͞␣B-crystallin, which is 90% identical to that of other mammals, has been detected in the eye and other tissues by reverse transcription-PCR (30).…”
Section: ␣-mentioning
confidence: 77%
“…Crystallins have been observed previously in lenses of the mole rat, S. ehrenbergi, by immunofluorescence (29). In addition, mole rat shsp͞␣B-crystallin, which is 90% identical to that of other mammals, has been detected in the eye and other tissues by reverse transcription-PCR (30).…”
Section: ␣-mentioning
confidence: 77%
“…In terms of sequence and structure, ␥S is an outlying member of the ␥-crystallin family, and it has been suggested that it might represent a hypothetical ancestor of the ␥-crystallins, possibly predating their recruitment to the lens (35,48,49). This family in turn belongs to the wider ␤␥-crystallin superfamily, which has members in both prokaryotes and eukaryotes (14,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Using the computer graphics program FRODO (Jones, 1978), bovine yS-crystallin has already been modeled based on the coordinates of bovine yB-crystallin (Quax-Jeuken et al, 1985).…”
mentioning
confidence: 99%